Waste Management Practices of the United States Antarctic Program - Reed, Sherwood C.; Sletten, Robert S. (1989)
The United States operates research facilities in Antarctica, at Coastal locations, inland sites, and on the interior snowfield. This report documents the results of 1988 investigations and evaluations of present waste management practices at these stations and recommends future action. In addition to liquid and solid waste management, the report discusses related water supply issues. Keywords: Sewage disposal; Solid wastes; Waste treatment; Water supply.